The behavior of University Students Cheating in Tests Under Emergency Online Teaching Modalities by Academic Regulations. (Innovaciones Educativas, 2022)
This work is based on the social problems that university students' fraudulent habits can generate. Also, students' behavior concerning fraudulent practices associated with cheating in evaluations while teaching under the modality in emergency online teaching environments according to academic regulation is studied. We offer an analytic perspective on 60 students of the quantitative courses of economic sciences at three public universities in Costa Rica. The article focuses on an exploratory type of research developed through a qualitative data collection design; through fieldwork. In the context of education under emergency online teaching environments, the data obtained from the population interviewed shows a marked decrease in the realization of bad habits of fraud in course evaluations. Furthermore, students in these environments have the possibility of being able to consult the didactic materials that are used throughout the course as support for carrying out the tests. Through the investigation, it is possible to identify the main reasons that influence students to cheat in university academic evaluations, analyzing how emergency online teaching environments promote fraudulent habits supported by the technological resources available to students.
Keywords: Assessment system; academic fraud; alternative teaching; pedagogical innovation; summative assessment; university student